Associations Between Carotid Plaque Characteristics and Perioperative Cerebral Blood Flow Determined by Arterial Spin Labeling Imaging in Patients With Moderate-to-Severe Stenosis Undergoing Carotid Endarterectomy - Liu, Ying; Huo, Ran; Xu, Huimin; Zhou, Guangjin; Wang, Tao; Yuan, Huishu; Zhao, Xihai (Frontiers in Neurology, 2022)
Purpose: To examine the associations between carotid plaque characteristics and perioperative cerebral blood flow (CBF) by arterial spin labeling (ASL) imaging. Materials and methods: Patients with unilateral moderate-to-severe carotid stenosis referred for carotid endarterectomy (CEA) were recruited and underwent carotid vessel wall and brain ASL magnetic resonance imaging. The relative CBF (rCBF = CBFindex-hemisphere/CBFcontralateral-hemisphere) in the middle cerebral artery territory, plaque burden and the presence of lipid-rich necrotic core, intraplaque hemorrhage (IPH), calcification, ulcer and fibrous-cap rupture, volume and maximum plaque components’ area percentages were measured. The associations between plaque characteristics and perioperative CBF were analyzed. Results: Sixty-one patients (age, 66.6 ± 7.8 years; 55 males) were included. Univariate linear regression showed that rCBFpre-CEA was associated with stenosis (β, –0.462; 95% confidence interval [CI], –0.797 to –0.126; P = 0.008), calcification (β, 0.103; 95% CI, 0.005–0.201; P = 0.040), maximum IPH area percentage (β, –0.127; 95% CI, –0.223 to –0.030; P = 0.012), and ulcer (β, 0.069; 95% CI, 0.025–0.113; P = 0.005). rCBFpost-CEA was associated with the IPH volume (β, –0.060; 95% CI, –0.107 to –0.014; P = 0.013). After adjusting for confounding factors, the associations of calcification with rCBFpre-CEA (β, 0.099; 95% CI, 0.004 to –0.194; P = 0.042) and IPH volume with rCBFpost-CEA (β, –0.060; 95% CI, –0.109 to –0.011; P = 0.020) remained statistically significant, while those of rCBFpre-CEA with maximum IPH area percentage (β, –0.089; 95% CI, –0.188 to 0.011; P = 0.080) and ulcer (β, 0.050; 95% CI, –0.012 to 0.112; P = 0.100) did not. Conclusion: Compositional characteristics of carotid atherosclerotic plaques, particularly IPH, were associated with perioperative CBF in patients with unilateral moderate-to-severe carotid stenosis undergoing CEA. Our findings indicated that patients with larger carotid IPH could expect smaller improvement in CBF following CEA.